Central venous catheter‐related blood stream infection with pyomyositis due to Stenotrophomonas maltophilia after allogeneic bone marrow transplantation in a patient with aplastic anemia. (6th January 2016) - Kodama, Yuichi; Okamoto, Yasuhiro; Tanabe, Takayuki; Nishikawa, Takuro; Abematsu, Takanari; Nakagawa, Shunsuke; Kurauchi, Koichiro; Shinkoda, Yuichi; Ikeda, Naohiro; Seki, Shunji; Wakiguchi, Hiroyuki; Miyazono, Akinori; et al.
Abstract: Stenotrophomonas maltophilia causes pneumonia and CVC‐CRBSI in HSCT. However, there are few reports of pyomyositis due to S. maltophilia . We report a patient with CRBSI and pyomyositis due to S. maltophilia after allogeneic HSCT who was successfully treated by removing the CVC and antibiotics without surgical drainage. Removing the CVC and the combined antibiotics without preventing the neutrophil engraftment could avoid surgical drainage in pyomyositis due to S. maltophilia when detected in an early stage.